Does CSR Expense Affect Indonesian Listed Firms’ Capital Structure Over Their Life-Cycle? - Witjaksono, Aryo Dimas; Nainggolan, Yunieta Anny (Journal of Business and Management, 2020)
Abstract. This final project aims to examine the association between corporate social responsibility (CSR) expenses and capital structure throughout the corporate life cycle in Indonesian listed companies. This research develops a hypothesis that are tested empirically through multivariate settings with robust standard errors. The tests are conducted using a sample of 527 Indonesian listed firms and 901 firm-year observations between 2010 and 2015. The findings support the hypothesis that CSR expenses are inversely related with debt to equity ratio throughout their life cycle. For investors, to invest in firms that have high CSR expense, high retained earnings and more matured firms with lower growth rate would indicate that the firm tends to keep lower debt to equity ratio over its life cycle which may be a factor to be considered when choosing an investment. For firm managers, disclosing the CSR expenditures transparently might help investors to be able to make considerations on whether or not to invest in the firm.. To the best of the author’s knowledge, there is thin literature investigating the relation between CSR and capital structure throughout corporate life cycle in emerging markets and its urgency as it may encourage companies to integrate CSR practice into their business strategy and transparently disclose their CSR activities. This final project contributes to the existing literature by examining these topics in a country where CSR is mandatory by the law.Keywords: Indonesia, Corporate social responsibility, Capital structure, Corporate life cycle